2018
DOI: 10.1039/c8cc05645e
|View full text |Cite
|
Sign up to set email alerts
|

Anthranilamide (aam)-substituted diboron: palladium-catalyzed selective B(aam) transfer

Abstract: An unsymmetrical diboron bearing an anthranilamide (aam) substituent was synthesized and was found to be coupled with aryl halides through the palladium-catalyzed Miyaura-Ishiyama-type reaction. The selective transfer of aam-substituted boryl moiety led to exclusive formation of diverse Ar-B(aam).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…The next step was to assess the antiplasmodial activity in vitro against P. falciparum strain, but this raised concerns as to the potential aqueous stability of compound 2. Indeed, benzo[d][1,3,2]diazaborin-4-ones obtained from anthranilamide are reported to be a protecting group for boronic acids and able to generate air-stable boronic acid precursors [11][12][13]. Davies et al reported relative stability in neutral or acid pH for their benzo[d][1,3,2]diazaborin-4-ones derivatives, but with very small amounts of D 2 O (from 6 to 16 µL).…”
Section: Discussionmentioning
confidence: 99%
“…The next step was to assess the antiplasmodial activity in vitro against P. falciparum strain, but this raised concerns as to the potential aqueous stability of compound 2. Indeed, benzo[d][1,3,2]diazaborin-4-ones obtained from anthranilamide are reported to be a protecting group for boronic acids and able to generate air-stable boronic acid precursors [11][12][13]. Davies et al reported relative stability in neutral or acid pH for their benzo[d][1,3,2]diazaborin-4-ones derivatives, but with very small amounts of D 2 O (from 6 to 16 µL).…”
Section: Discussionmentioning
confidence: 99%
“…232–234℃ (Lit. 230.1–233.3℃ (Kamio et al., 2018)); ν max (ATR) 752, 1,179, 1,273, 1,569, 1,640, 3,299, 3,359 cm −1 ; 1 H‐NMR (DMSO‐ d 6 ) 3.79 (3H, s, ‐OCH 3 ), 6.99 (2H, d, J = 8.5 Hz, H‐3′,5′), 7.07 (1H, t, J = Hz, H‐6), 7.41 (1H, d, J = 8.0 Hz, H‐8), 7.54 (1H, dt, J = 1.5 and 8.5 Hz, H‐7), 8.01 (1H, d, J = 8.5 Hz, H‐4), 8.03 (2H, d, J = 8.5 Hz, H‐2′,6′), 9.19 (1H, s, NH), 9.61 (1H, s, NH); 13 C‐NMR (DMSO‐ d 6 ) 55.4, 118.5, 119.1, 121.0, 124.0, 28.4, 133.8, 135.5, 146.1, 161.8, 166.8; HRMS (ES): m / z [ M + H] + calc for C 14 H 14 BN 2 O 2 : 253.1148; found 253.1148.…”
Section: Methodsmentioning
confidence: 99%
“…In 2018, Yoshida reported the first synthesis of aam‐substituted unsymmetrical diboron, (pin)B−B(aam), from bis(pinacolato)diboron, (pin)B−B(pin), and aam‐H 2 in refluxing chlorobenzene, aiming at the development of direct B(aam)‐installing reactions (Scheme 5). [10] Although it took 48 h for the preparation under the conventional heating conditions, the reaction time was considerably shortened under microwave irradiation conditions (250 °C) without apparent yield loss.…”
Section: Preparation Of B(aam)‐installing Reagentsmentioning
confidence: 99%
“…The aam‐substituted diboron, (pin)B−B(aam), was coupled with aryl halides through the palladium‐catalyzed Miyaura–Ishiyama‐type reaction [10] . The selective transfer of aam‐substituted boryl moiety led to exclusive formation of diverse Ar–B(aam)s (Scheme 7).…”
Section: B(aam)‐installing Reactionsmentioning
confidence: 99%